2022
DOI: 10.1007/s12237-022-01115-4
|View full text |Cite
|
Sign up to set email alerts
|

Historic Spatial Patterns of Storm-Driven Compound Events in UK Estuaries

Abstract: Compound estuarine flooding is driven by extreme sea-levels and river discharge occurring concurrently, or in close succession, and threatens low-lying coastal regions worldwide. We hypothesise that these drivers of flooding rarely occur independently and co-operate at sub-daily timescales. This research aimed to identify regions and individual estuaries within Britain susceptible to storm-driven compound events, using 27 tide gauges linked to 126 river gauges covering a 30-year record. Five methods were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Here, the extreme wind event is likely a storm that is paired with storm surge and/or extreme precipitation, commonly referred to as a compound flood. Various research has shown that these compound floods occur most frequently as a consequence of European winter storms 54,55 , however, they can also occur during summer with devastating impacts, as has been observed during the July 2021 UK floods 56 . Likewise, floods are prominent in Bangladesh, in a flood to flood hazard pair.…”
Section: Resultsmentioning
confidence: 95%
“…Here, the extreme wind event is likely a storm that is paired with storm surge and/or extreme precipitation, commonly referred to as a compound flood. Various research has shown that these compound floods occur most frequently as a consequence of European winter storms 54,55 , however, they can also occur during summer with devastating impacts, as has been observed during the July 2021 UK floods 56 . Likewise, floods are prominent in Bangladesh, in a flood to flood hazard pair.…”
Section: Resultsmentioning
confidence: 95%
“…Here, the extreme wind event is likely a storm that is paired with storm surge and/or extreme precipitation, commonly referred to as a compound flood. Various research has shown that these compound floods occur most frequently as a consequence of European winter storms 54 , 55 , however, they can also occur during summer with devastating impacts, as has been observed during the July 2021 UK floods 56 . Likewise, floods are prominent in Bangladesh, in a flood to flood hazard pair.…”
Section: Resultsmentioning
confidence: 96%
“…Here, the extreme wind event is likely a storm that is paired with storm surge and/or extreme precipitation, commonly referred to as a compound ood. Various research has shown that these compound oods occur most frequently as a consequence of European winter storms 53,54 , however, they can also occur during summer with devastating impacts, as has been observed during the July 2021 UK oods 55 . Likewise, oods are prominent in Bangladesh, in a ood to ood hazard pair.…”
Section: Multi-hazard Pairsmentioning
confidence: 95%